Modulation of signals in optical systems - Abdullah, Mohammad Khazani; Dimyati, Kaharudin; Abas @ Ismail, Ahmad Fauzi; Endut, Rosdisham; Abdullah, Fairuz (2007)
A method for modulating signals in an optical system comprises generating a digital electrical input signal, dividing the signal into two parts, passing one part of the signal to an electrical inverter, converting the un-inverted and inverted electrical signals to un-inverted and inverted optical signals of different wavelength or of the same wavelength but differently encoding, combining the two optical signals into a single optical fibre, separating the combined signals into an un-inverted and an inverted optical signal, reconverting the two optical signals to two electrical signals, determining the difference in voltage between corresponding bits of the two signals and generating a digital electrical output signal based on that difference. The invention also includes a modulation arrangement for use in the method.